Relação da expressão do trop2 com fatores clínico-patologicos, sobrevivência e resposta à quimioterapia em pacientes com câncer de mama triplo negativo - Oliveira, Jailson de Sousa (2024)
INTRODUCTION: Triple Negative Breast Cancer (TNBC) is a subtype that does not express hormone receptors and HER-2 protein, which makes it more aggressive. TROP2 is a transmembrane protein that may be expressed in TNBC and has been associated with clinicopathological factors of greater tumor aggressiveness and worse survival outcomes. There are limited data on the role of TROP2 in the setting of Localized TNBC and its possible value as a prognostic factor and predictor of response to treatment. OBJECTIVES: To analyze the expression of TROP2 in Triple Negative Breast Cancer at early and locally advanced stages and explore possible relationships with clinicopathological characteristics, response to neoadjuvant treatment and survival outcomes MATERIAL AND METHODS: The study followed a cross-sectional, retrospective model, with the target population being patients diagnosed with TNBC Stages I, II or III from January/2012 to December/2020. The sample consisted of 54 patients selected using a non-probabilistic technique for convenience, from January 1, 2012 to December 31, 2020. To collect the data, electronic medical records, biopsy material from the primary tumor and a form prepared by the authors. RESULTS: The average age of the patients was 51 years with a range from 28 to 86 years. The majority of tumors in our study were classified as ductal carcinoma histological subtype, which corresponded to 34 patients (62.9%). The presence of lymphovascular invasion (ILV) and perineural invasion (IPN) were present in 46.2% (n=25) and 18.5% (n=10) of patients. Regarding clinical staging at diagnosis, it was observed that the majority presented Stage III corresponding to 27 patients (50%) while 22 patients (40.7%) presented Stage II and only 5 patients (9.2%) presented Stage I. Immunohistochemical evaluation showed that TROP2 staining showed membranous positivity, and in most cases it was of variable intensity throughout the tumor, with staining being exclusively in tumor cells. Evaluation of TROP2 expression by immunofluorescence in the 54 patients showed that 39 (72.2%) patients had low TROP2 expression and 15 (27.8%) patients had high expression. The global assessment of TROP2 expression showed that 90.7% (n=49/54) of patients had some TROP2 expression. High TROP2 expression was significantly associated with the presence of lymphatic vascular invasion, tumor size and higher staging. When samples from 26 patients who underwent neoadjuvant chemotherapy were evaluated, a significant association was observed between high TROP2 expression (>37.5%) and a higher rate of complete pathological response. CONCLUSION: TROP2 expression was associated with clinicopathological factors and contributed to a greater response to chemotherapy in patients with triple-negative breast cancer.